Association between obesity and sedentary behavior in adults - Bárbara de Barros Gonze; Thatiane Lopes Valentim di Pachoale Ostolin; Evandro Fornias Sperandio; Rodolfo Leite Arantes; Antônio Ricardo de Toledo Gagliardi; Marcello Romiti; Victor Zuniga Dourado (Universidade Federal de Santa Catarina, 2021)
Although sedentary behavior (SB) is related to the development of metabolic diseases, there is still no consensus in literature about the association between accelerometer-based SB and obesity, especially adjusted for cardiovascular risk factors and level of daily physical activities. The aim was to evaluate the association between obesity and SB adjusted for potential confounders in adults. Data from 780 participants of the Epidemiology and Human Movement (EPIMOV) Study were analyzed. Body weight, body mass index (BMI), and fat body mass as percentage (%FBM) (bioelectrical impedance) were obtained and, then, used to stratify participants. SB was objectively measured using triaxial waist-worn accelerometers placed above the dominant hip during waking hours for at least four consecutive days (4-7 days). SB and its pattern were not significantly different between obesity groups. Although SB presented some significant correlations with obesity, the correlation and determination coefficient indicated weak association between SB and obesity (e.g., BMI and %FBM). Obesity presented little or no association with SB and its pattern after adjustment for potential confounders, especially when  SB is measured through accelerometry.